Analysis of Student Learning Interest by Using Google Classroom on Online Learning for Engineering Physics Courses - Inung Diah Kurniawati (International Journal of Basic and Applied Science, 2022)
Online learning has been implemented since the COVID-19 pandemic hit the world. Google Classroom is one of the media that can be used for online learning. By utilizing Google Classroom, it is expected to increase student learning interest. The purpose of this study was to analyze student interest in learning by utilizing google classroom in Engineering Physics course. This type of research is descriptive quantitative research. The subjects of this research are students of Electrical Engineering, PGRI Madiun University who are taking Engineering Physics courses. Research data obtained by distributing questionnaires to respondents. The questionnaire contains indicators of learning interest which consists of 4 indicators. The data obtained were then analyzed using a descriptive percentage analysis technique, which was then interpreted by category to then get a good conclusion. The results showed that the interest in learning of Electrical Engineering students in online lectures using Google Classroom was in a good position with a percentage value of 65.74%.